Improving agricultural pollution abatement through result-based payment schemes. (September 2018) - Sidemo-Holm, William; Smith, Henrik G.; Brady, Mark V.
Highlights: Result-based payments incentivize cost-effective agricultural pollution abatement. Farmers adopt fewer but more effective abatement measures when paid based on results. Less pollution and more crop production with result-based payments. Abatement results and ensuing payments can be calculated by modeling abatement. Abstract: Action-based payments that compensate farmers for adopting land-management measures to preserve and enhance the environment have been criticized for being ineffective. The root of the problem is that farmers are not paid for achieving a desired environmental benefit, but compensated for their costs of management. There is growing interest in formulating result-based economic incentives. By paying for an environmental benefit and allowing flexibility in how to achieve it, farmers are given an incentive to exploit their comparative advantages for achieving a desired environmental benefit cost-effectively. However, the feasibility and relative effectiveness of result-based payments for reducing agricultural pollution is contentious. In this study, we designed and evaluated a result-based payment scheme for nonpoint-source pollution abatement from arable land. In a case study in southern Sweden, the cost-effectiveness of the new scheme was compared with that of an existing action-based scheme for vegetated buffer strips to prevent the pollutant, particulate phosphorus, from reaching water resources. The results suggest that result-based payment schemes based on modeled outcomes of pollution abatement are feasible and will considerably improve cost-effectiveness compared to action-based schemes, by relocating buffer strips to where they are more effective and not simply where they have the lowest costs for farmers.